A comparison of the sensory and rheological properties of different cellulosic fibres for food - Agarwal, Deepa; Hewson, Louise; Foster, Tim (Royal Society of Chemistry, 2018)
The impact of different cellulosic microstructures formed by highly entangled fibre networks 8 were studied for food applications as dietary fibre. This paper reports the impact of microstructure on the rheological and sensory behaviour of the aqueous suspensions of particulate and fibrillated forms of softwood cellulosic fibres, and were compared with citrus fibre. An aqueous suspension of cellulosic fibres shows stable viscoelastic gel-like behaviour as a function of frequency. The particulate form of cellulosic fibres showed lowest shear viscosity as compared to the entangled network system at comparable concentrations. To provide further insight into the relationship between the structure of cellulosic fibre systems and perception of salt taste in aqueous suspensions of softwood cellulosic fibres (fibrillated and particulate form) and citrus fibres with matched shear viscosities were studied. A hypothesis to explain why softwood cellulosic fibre (CTE) with entangled network structure prolongs the taste perception is presented.